2008
DOI: 10.1108/09600030810900969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the integration of seaport container terminals in supply chains

Abstract: Purpose -The purpose of this paper is to define and empirically develop measures to evaluate the extent of integration of seaport container terminals in supply chains. Design/methodology/approach -A literature review identified four key variables hypothesized to be part of the higher-order construct of "terminal supply chain integration (TESCI)". The hypotheses were theoretically justified a priori and data for operationalizing the conceptualized variables obtained via a large-scale survey of container termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 76 publications
2
91
0
3
Order By: Relevance
“…In this case, network integration can be achieved by extending their seaport terminal into, for example, inland terminals in the hinterland (e.g., Veenstra, Zuidwijk, and Van Asperen 2012). Literature has identified linkages between port integration practices and significant improvements in terms of productivity, cost reduction, delivery quality, and shorter cycle time and the effectiveness of the supply chain as a whole (Panayides and Song 2008;Woo, Pettit, and Beresford 2013). In our knowledge, however, hardly any research has developed a structured and comprehensive understanding of how ports can achieve supply chain integration.…”
Section: Port Supply Chain Integration: a Conceptual Frameworkmentioning
confidence: 97%
“…In this case, network integration can be achieved by extending their seaport terminal into, for example, inland terminals in the hinterland (e.g., Veenstra, Zuidwijk, and Van Asperen 2012). Literature has identified linkages between port integration practices and significant improvements in terms of productivity, cost reduction, delivery quality, and shorter cycle time and the effectiveness of the supply chain as a whole (Panayides and Song 2008;Woo, Pettit, and Beresford 2013). In our knowledge, however, hardly any research has developed a structured and comprehensive understanding of how ports can achieve supply chain integration.…”
Section: Port Supply Chain Integration: a Conceptual Frameworkmentioning
confidence: 97%
“…The authors suggested that these parameters form a basis for the exact attributes that contribute to port competitiveness in the supply chain. Panayides and Song (2008) extended the previous work by developing a measurement instrument that can be used by researchers to measure the extent to which a port or container terminal is supply chain oriented. Via a survey of container terminal operators in Europe and East Asia, the constructs were validated using confirmatory factor analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Via a survey of container terminal operators in Europe and East Asia, the constructs were validated using confirmatory factor analysis. Tongzon et al (2009) studied the port of Incheon as a case in point and measured the degree of its supply chain orientation based on the indicators developed by Panayides and Song (2008). The study found that ports or terminals in practice may not be supply chain oriented as theories predict.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is well established in the literature that maritime transport services should be studied in the context of the supply chain that they are embedded in, as supply chain management is now widely practiced by industry professionals (Robinson 2002;Christopher 2005;Carbone and Gouvernal 2007;Cahoon and Notteboom 2008;Zhang and Huang 2012). Many research papers have studied ports from a supply chain perspective, for example, the value propositions and strategic roles of ports/terminals (Robinson 2002;Paixão and Marlow 2003;Robinson 2006;Mangan, Lalwani, and Fynes 2008;Rodrigue and Notteboom 2009;Zhang, Lam, and Huang Fothcoming), port/terminal integration in the supply chain (Carbone and De Martino 2003;Panayides and Song 2008;Song and Panayides 2008;Panayides and Song 2009;Tongzon, Chang, and Lee 2009), port performance measurements (Marlow and Paixão Casaca 2003;Bichou and Gray 2004), and port competition in supply chain systems Yap 2011a, 2011b). Surprisingly, very few papers (Vernimmen, Dullaert, and Engelen 2007;Notteboom and Rodrigue 2008;Saldanha et al 2009;Lam and Van De Voorde 2011) have adopted a supply chain perspective to study liner shipping services.…”
Section: Introductionmentioning
confidence: 97%